Faktor yang Mempengaruhi Minat Sarjana Pertanian Fakultas Pertanian UNS untuk Bekerja di Bidang Pertanian - Ashlih Ricky Maulana; Suminah Suminah; Eksa Rusdiyana (Universitas Sebelas Maret, 2021)
This study aims to (1) determine the interest of graduates of the Faculty of Agriculture Universitas Sebelas Maret (UNS) Surakarta to work in the agricultural sector, (2) to examine the factors that influence the interest of graduates of the Faculty of Agriculture UNS to work in the agricultural sector, (3) to examine how the influence of factors that influence the interest of graduates of the Faculty of Agriculture UNS to work in the agricultural sector. This research was carried out at the Faculty of Agriculture, UNS Surakarta. The method used in this study is a quantitative research method with survey techniques. The population in this study were alumni of the faculty of agriculture who graduated in 2019. The data processing was carried out by researchers using the classical assumption test, which consisted of normality test, linearity test, multicollinearity test and heteroscedasticity test. After completing the classical assumption test, the data analysis was continued with regression testing, F-test and T-test. The results showed that: (1) the interest of UNS agricultural graduates to work in agriculture was mostly in the high and sufficient category. (2) The perception factor of work in agriculture, experience, lifestyle, family environment and the closest social environment simultaneously have a significant influence on the interest of graduates of the Faculty of Agriculture UNS to work in the agricultural sector. (3) The perception factor of work in agriculture, lifestyle, family environment and the closest social environment partially has a significant influence on the interest of graduates of the Faculty of Agriculture UNS to work in the agricultural sector, while the experience factor partially does not have a significant influence.